Homoeopathy for Allergic Rhinitis (Homoeopathy for All, 2025)
Allergic rhinitis (commonly called  hayfever) is an inflammation or  irritation of the mucous membranes  that line the nose. Common  symptoms include sneezing; a stuffy  or runny nose; itchy eyes, nose and  throat;and watery eyes. The patient  may havea nasal voice; breathe  noisily; snore; feel chronically tired;  have a poorappetite; feel nauseated;  have frequent headaches; and, have  somedifficulty hearing and smelling.
Keywords: sneezing; poorappetite